Sporazumevalna zmožnost - eden izmed temeljnih ciljev pouka slovenščine - Bešter, Marja (Jezik in slovstvo, 2011)
Developing communicative competence in Slovene is one of the principal goals of teaching Slovene based on the contemporary curriculum for primary schools. The article first presents the conception and models of communicative competence as treated in foreign and domestic literature, then the interpretation and ways of developing communicative competence in the classroom, as determined by the updated curriculum for Slovene (2011).
Keywords: Slovene; Slovenian language; slovenščina; didaktična metoda; teaching method; teaching objective; učni cilj; sporazumevanje; jezikovna didaktika; sporazumevalna zmožnost; pouk slovenščine; jezikovni načrti; osnovna šola; primary school